Occupational Safety And Health Of Women Workers In Semiconductor Assembly In Relation To Chemical Exposure - Ng, Wei Khiang (2001)
Semiconductor assembly is a chemical intensive industry. Some of the chemicals involved in the assembly of chips have been reported to cause health problems to the workers. This study w as carried out to examine the health problems of the workers in relation to the chemicals that they used. The study was carried out in 12 semiconductor factories in the Bayan Lepas Free Trade Zone, Penang. The study comprised of four stages, (i) management survey, (ii) factory walk-through, (iii) worker survey using structured questionnaire and (iv) an interview with the safety and health officer on chemical safety management. A total of 655 women workers participated in the study. Results showed that the used of chemicals by respondents was associated with work sections (X2 = 94.0 5, p<0. 00I ), with middle of line (68. 3%) having relatively higher number of respondents who use chemicals compared to front of line (37. 9%) and end of line (21.4 %). Results also showed that skin itchiness (31. 5%, n=222) was the most common general health complaint, followed by eye problem (20 .3%) and breathing difficulty (19.4 %).